Alternative Phillips curves models with endogenous real-time expectations - David Kiefer (The University of Utah, Department of Economics, 2010)
Originally presented as an empirical regularity, a variety of microeconomic derivations of the Phillips tradeoff between inflation and real output have been developed. Since these new Phillips curve models are expressed in terms of unobserved variables and expectations, we develop estimates of these unobservables using a state space characterization of the short-run political-economic equilibrium. This method is appropriate because it yields recursive forecasts based on contemporaneous information, and because we apply it to a real-time data set in order to accurately measure available information. Although none of the new Phillips curve tested are completely adequate, we find that Calvo's sticky price formulation provides the best fit for US data. It is inadequate because the estimate coefficient for the driving variable (either the output gap or the marginal cost) is essentially zero.
Keywords: E3; E6; 330; new Phillips curve; microfoundations; real-time data; Phillips-Kurve; Erwartungstheorie; Theorie; Schätzung; USA